From Plant Chemistry to Reproducible Antidiabetic Products: A Critical Review of Molecular Targets, Clinical Evidence, and Translational Gaps - Pirscoveanu Denisa Floriana Vasilica; Diana-Maria Trasca; Adina Maria Kamal; Renata Maria Varut; Daniela Cîrțînă; Romeo Popa; Pluta Ion Dorin; Dîrnu Rodica; Maria Stoica; Coancă-Staicu Cristina Teodora; George-Alin Stoica (Molecules, 2026)
Diabetes mellitus results from insulin resistance, progressive pancreatic β-cell dysfunction, dysregulated hepatic and adipose metabolism, oxidative stress, and inflammation. Plant-derived compounds can modulate several of these processes, yet pharmacological breadth does not necessarily produce a reproducible therapy. This critical narrative review links phytochemical identity and product composition to intestinal carbohydrate digestion, insulin secretion, hepatic glucose production, GLUT4 trafficking, AMPK and PPARγ signaling, the incretin–DPP-4 axis, renal glucose handling, and diabetic organ injury. Alkaloids, flavonoids, phenolic acids, tannins, saponins, and polysaccharides are considered alongside evidence concerning nephropathy, neuropathy, ocular disease, hepatopathy, and cardiomyopathy. Controlled human studies provide product-specific signals, particularly for chemically defined berberine preparations and mulberry alkaloids, whereas most other interventions remain supported by small, short, or chemically undercharacterized trials. The strongest candidates are those for which defined chemistry, plausible exposure, mechanism, and controlled clinical findings converge. Progress requires authenticated raw material, validated analytical fingerprints, pharmacokinetic and toxicological characterization, herb–drug interaction testing, and trials using the same standardized product. These interventions should remain supervised adjuncts or drug-discovery leads rather than substitutes for established diabetes treatment.